Lanzamiento de muebles de cartón para la categoría hogar - Salomon Bernedo, Naif (2022)
This research seeks to determine if the launching of furniture made with cardboard for the furniture market can meet a possible unmet consumer demand. With the information gathered from surveys and an interview with an expert in the cardboard furniture business, it has been determined that the launching of these products can satisfy consumers' need for furniture that is environmentally friendly, practical and easy to install. The main recommendation before launching a new product on the market is to conduct the necessary surveys and interview an industry expert to first determine the level of acceptance. With this, a more in-depth study of the market can begin. Finally, the information gathered in this research seeks to support future studies that decide to undertake a cardboard furniture business that is committed to the environment and represents a solution for consumers. Therefore, this study can be used as a reference and adapted as appropriate.